EDUKASI DAN STRATEGI DALAM MENGANTISIPASI PERILAKU KEKERASAN SEKSUAL PADA REMAJA DI SMAN 5 PEKANBARU - Ratu Husna Aulia; Nabila Ariyanda; Tiara Syahfitri; Yuhelsa Marsanda; Lexa Putri Amanda; Aufa Nur Asyifa; Zahratul Alya Anwar; Zakia Aulia Zikra; Ilham Hudi (CV. Denasya Smart Publisher, 2026)
Cases of violence and sexual crimes continue to increase and have become a complicated and very important issue among the overall crimes experienced by women. Sexual violence is rampant among female students in schools. Cases of sexual violence against children are triggered by the low level of sexual education, which is considered taboo and inappropriate for children. The aim of this activity is to raise awareness and strengthen efforts to prevent and address sexual violence in teenage and school environments. This education is carried out using a socialization method. The results of this activity show an increase in knowledge related to the prevention and handling of sexual violence.